The Juridical Analysis of Land Ownership Rights Purchased Prior to Making a Marriage Agreement (Postnuptial Agreement) - Asmara, Diah Kumala (Jurnal Konstatering, 2022)
This research aims toknow and analyzeregarding the juridical analysis of land ownership rights purchased prior to the conclusion of a postnuptial agreement on a marriage, as well asknow and analyze aboutthe role and authority of a Notary in making a marriage agreement deed for land ownership purchased before the marriage.The approach method in this research is normative law (doctrinal). Normative legal research that is more specific discusses legislation or is also called normative juridical. Based on the results of the study concluded: 1)Marriage agreements made while in a marriage bond can be carried out after the decision of the Constitutional Court Number69/PUU-XII/2015, while regarding land purchased before the marriage agreement is made it will remain joint property as stipulated in Article 35 paragraph (1) of the Marriage Law, because marriage agreements made while in a marriage bond only bind to the assets that will be obtained later after the marriage agreement was made. The same goes for theorylegal certainty in the opinion of Gustav Radbruch, in principle has been well fulfilled considering that the marriage agreement is made as a legal means to protect the rights and obligations of the husband and wife when the marriage life takes place, which is made in accordance with the agreement of the parties to be ratified by the employee of the Marriage Registrar or Notary; 2)The role and authority of the Notary in the marriage agreement is based on the addition and change of phrases made by the Constitutional Court to the formulation of Article 29 paragraph (1) of Act No. 1 of 1974 concerning Marriage, which is connected with the phrase ".....after which the contents also apply to third parties as long as a third party is involved" is still maintained by the Constitutional Court, it is found that the Constitutional Court gives new authority to Notaries to ratify marriage agreements with third party binding purposes. In this case it can be said that the role of the Notary is to ratify the existing marriage agreement and not to make marriage agreements. This is due to the change in the phrase "enter into a written agreement" to "submit a written agreement".Keywords: Debt; Outstanding; Tax.